Test of CP-invariance of the Higgs boson in vector-boson fusion production and in its decay into four leptons - Aad, G; Abbott, B; Abeling, K; Abicht, NJ; Abidi, SH; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; Abusleme Hoffman, AC; Acharya, BS; Adam Bourdarios, C; et al. (Springer, 2024)
A search for CP violation in the decay kinematics and vector-boson fusion production of the Higgs boson is performed in the H → ZZ* → 4ℓ (ℓ = e, μ) decay channel. The results are based on proton-proton collision data produced at the LHC at a centre-of-mass energy of 13 TeV and recorded by the ATLAS detector from 2015 to 2018, corresponding to an integrated luminosity of 139 fb−1. Matrix element-based optimal observables are used to constrain CP-odd couplings beyond the Standard Model in the framework of Standard Model effective field theory expressed in the Warsaw and Higgs bases. Differential fiducial cross-section measurements of the optimal observables are also performed, and a new fiducial cross-section measurement for vector-boson-fusion production is provided. All measurements are in agreement with the Standard Model prediction of a CP-even Higgs boson.